Use of Interactive Presentations to Improve the Presentation and Learning Interest of Integrated Islamic Elementary School Students - Yusron, Ali (Al-Hijr: Journal of Adulearn World, 2024)
Teachers in elementary schools tend to teach in a watching style. Even though there are more effective ways to use so that students quickly understand the lesson, for example using interactive presentations. The purpose of this study is to determine the improvement of teaching and learning interest in Integrated Islamic Elementary Schools by using interactive presentations. This study uses a quantitative method using a survey model and in-depth interviews to the audience. The survey used in this study is online based. The results of this study show that students' interest in learning increases after teachers implement interactive presentations in learning. The conclusion of the study explains that the use of this learning model is very helpful for teachers of Integrated Islamic Elementary Schools in teaching and learning, so that students' interest in learning increases. Therefore, the limitations of this study, the researcher only conducted research on the use of interactive presentations to increase the learning interest of Integrated Islamic Elementary School students. The researchers hope that future researchers can use this method to improve junior high school students and also high school students.